Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech in Sierra Leone: A Rapid Scan - Mullan, Joel; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, in Sierra Leone. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Sierra Leone; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Education service transformation in Sierra Leone: Where policy meets the people | Blog | Global Partnership for Education - Sengeh, David Moinina (2020)
As GPE prepares to launch a new five-year strategic plan responding to partner countries’ demands for transformative change, GPE Board Member and Minister of Basic and Senior Secondary Education David Moinina Sengeh shares learnings from his first year of office on what transforming education means to the people of Sierra Leone.

Leh Wi Lan: Improving The Quality Of Secondary Education In Sierra Leone - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)

Transforming education service delivery in Sierra Leone: from evidence to action - Sengeh, David Moinina; May-Wilson, Hannah (Global Partnership for Education, 2020)
Sierra Leone’s education system has been plagued by events that have challenged the effective delivery of high-quality education for every child for nearly three decades. But thanks to a program launched in 2018, the government is achieving greater access, quality, and equity for children by removing financial barriers to school enrollment and improving teaching and learning outcomes.

Worldreader | Sierra Leone - Worldreader (2020)
Worldreader brings digital reading to schools in Sierra Leone in partnership with the Klintworth Family Foundation.

Government–donor relations in Sierra Leone: Who is in the driving seat? - Harris, David; Conteh, Felix Marco (The Journal of Modern African Studies, 2020)
Since the cessation of conflict in 2002, Sierra Leone has experienced extraordinary levels of involvement from Western donors. Paradoxically, while relationships are often portrayed on the ground as strong with significant donor influence, our research shows considerable fluidity in individual and institutional relationships. The article disaggregates donor–government relations at various levels over a short but crucial period, 2010–16, asking in each case who occupies the driving seat. In so doing, the article interrogates the concept of ‘extraversion’, investigating to what extent government – and indeed donors – has space in which to manoeuvre and how and why government and donors act as they do in this space. The period 2010–16 is of particular interest due to extreme iron ore price volatility and the Ebola epidemic of 2014–15. The article adds much-needed critique and empirical evidence to the debate on donor influence and ‘extraversion’.

Sierra Leone Demographic and Health Survey 2019 - Statistics Sierra Leone (The DHS Program, 2020)
ICF

Orange Education Portal - Orange Sierra Leone (2020)

Universal Access Development Fund | Home - Universal Access Development Fund (Sierra Leone) (2020)

Schools ICT project - Universal Access Development Fund (Sierra Leone) (2020)

Scientists at DSTI go the extra mile to make it easier for children to get to school - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)
Mike Fabrikant, a software developer from Washington D.C., is embedded within the data science team at the Directorate of Science, Technology, and Innovation (DSTI) to support systems delivery. His workRead More

DSTI | Home - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)

Ministry of Information and Communications | Home - Ministry of Information and Communications (Sierra Leone) (2020)

EMIS | Education Management Information System - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)

COVID-19 Education Emergency Response Plan - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)

How the Government of Sierra Leone is improving its Education Data Hub - EdTech Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub, is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How the Government of Sierra Leone is improving its Education Data Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and students could access and use…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

President Bio Commissions Newly Constructed Dr Kadie Sesay Girls Secondary School In Port Loko - SN Radio (2020)
#sierraleone #presidentbio #fatimabio #sierraleoneparliament #sierranetworkproduction #sierranetwork #sierranetworkwanpotshow President Bio Commissions Newly Constructed Dr Kadie Sesay Girls Secondary School In Port Loko. Latest News Website: http://www.blog.snradio.net FaceBook: http://www.facebook.com/SierraNetwork... Youtube: http://www.youtube.com/Salone2Bad Twitter: http://twitter.com/sierra_n_salone Radio: http://SNRadio.net Radio TuneIn App: http://tun.in/sfgyD SoundCould 1: http://www.soundcloud.com/sierra-network SoundCould 2: https://soundcloud.com/sierra-network-sl SoundCould 3: https://soundcloud.com/sierra-network... Contact Us: info@snradio.net Sierra Network For All That Matters Sierra Leone

Mitigating COVID-19 impacts and getting education systems up and running again: Lessons from Sierra Leone - Davis, Edward; Berry, Chris (Global Partnership for Education, 2020)
Reflexions on some of the lessons from the Sierra Leone Ebola education response that could be relevant for countries facing shutdowns of their education systems due to the COVID-19 pandemic.

RECOVR Sierra Leone: Tracking the Effects of the COVID-19 Pandemic - Warren, Shana; Parkerson, Doug; Collins, Elliott (Innovations for Poverty Action, 2020)

Education service transformation in Sierra Leone: Where policy meets the people - Sengeh, David (2020)

Sierra Leone | Education and Literacy Statistics - UNESCO (2020)
...

COL in the Commonwealth: Sierra Leone - Commonwealth of Learning (2020)

How can Sierra Leone’s education response after Ebola help with the COVID-19 response? - Bangay, Colin (The Education and Development Forum (UKFIET), 2020)
This blog is written by Colin Bangay, Senior Education Adviser, Department for International Development (DFID). It aims to look at some practical and sensible lessons from the education response in Sierra Leone during the Ebola outbreak, to help others as they face closures of education systems. This blog was originally published on the Global Partnership […]

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (Education continuity during the Coronavirus crisis, 2020)

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)

About Us | Teaching Service Commission - Sierra Leone - Teaching Service Commission (Government of Sierra Leone, 2020)

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Education Sector Analysis: Assessing the enabling environment for gender equality - Republic of Sierra Leone; UNICEF; IIEP-UNESCO Dakar (2020)

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Education in Africa: What Are We Learning? - Evans, David; Acosta, Amina Mendez (2020)
Countries across Africa continue to face major challenges in education. In this review, we examine 145 recent empirical studies (from 2014 onward) on how to increase access to and improve the quality of education across the continent, specifically examining how these studies update previous research findings. We find that 64 percent of the studies evaluate government implemented programs, 36 percent include detailed cost analysis, and 35 percent evaluate multiple treatment arms. We identify several areas where new studies provide rigorous evidence on topics that do not figure prominently in earlier evidence syntheses. New evidence shows promising impacts of structured pedagogy interventions (which typically provide a variety of inputs, such as lesson plans and training for teachers together with new materials for students) and of mother tongue instruction interventions, as well as from a range of teacher programs, including both remunerative (pay-for-performance of various designs) and non-remunerative (coaching and certain types of training) programs. School feeding delivers gains in both access and learning. New studies also show long-term positive impacts of eliminating school fees for primary school and positive impacts of eliminating fees in secondary school. Education technology interventions have decidedly mixed impacts, as do school grant programs and programs providing individual learning inputs (e.g., uniforms or textbooks).
Keywords: ⛔ No DOI found

DSTI Education Data Hub - DSTI (2020)

Education Innovation Challenge - Reflection & Learning Summit Report - DSTI (2020)

Sierra Leone Free Education Project - World Bank (2020)

Education Workforce Management in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)

Sierra Leone Education Attendance Monitoring System - Teaching Service Commission (2020)

Country-level research review: Sierra Leone - Kallon Kelly, Christiana; Koomar, Saalim; Kreimeia, Adam; McBurnie, Chris; Mitchell, Joel; Myers, Christina (2020)
Keywords: dode_eth-src-eth

Teacher Management Policy for Sierra Leone - Teaching Service Commission (2020)
Keywords: _C:Sierra Leone SLE

Education Workforce Spatial Analysis in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)
Keywords: _yl:a; ⛔ No DOI found

SALCAB | Home - SALCAB (2020)

Education Workforce Recruitment and Matching in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Workforce Initiative, 2020)
Keywords: _yl:b; ⛔ No DOI found

Education Workforce Supply and Needs in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (the Education Commission; Fab Inc., 2020)
Keywords: ⛔ No DOI found

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (2020)

Systems-Level Analysis of Education Service Delivery in Sierra Leone - Education Partnerships Group (2020)

Innovative Education Workforce Analysis for More Equitable Education: Sierra Leone - Education Workforce Initiative (Education Commission, 2020)

Independent Reporting Mechanism (IRM): Sierra Leone Design Report 2019–2021 - Field, Tracey-Lynn (Open Government Partnership, 2020)

Sierra Leone Education Attendance Monitoring System (SLEAMS) Final Technical Report - Graham, Hannah; Kawa, Muniru; Lee, Philip; Malyon, Stephanie; Hayward, Harry; Conteh, Sheriff; Chandia, Gloria (Charlie Goldsmiths Associates, 2020)

Sierra Leone Education Attendance Monitoring System (SLEAMS) Pilot Phase: Inception Report - Kawa, Muniru; Graham, Hannah; Lee, Philip; Murray, Tobias; Malyon, Stephanie (Charlie Goldsmiths Associates, 2020)

Incidence of HIV, all (per 1,000 uninfected population) - Sierra Leone | Data - World Bank (2020)

Republic of Sierra Leone: Education sector analysis: assessing the enabling environment for gender equality - UNICEF (2020)

Education continuity during the Coronavirus crisis: Sierra Leone and Liberia Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (Rising Academy Network, 2020)

Cost Effective Approaches to Improve Global Learning What Does Recent Evidence Tell Us Are Smart Buys for Improving Learning in Low-and-Middle-Income Countries - Global Education Evidence Advisory Panel (World Bank; FCDO; Building Evidence in Education, 2020)

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?”  As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Effectiveness of Multimodal Microlearning for In-Service Teacher Training - Allela, Melisa Achoko; Ogange, Betty Obura; Junaid, Muhammad Ibn; Charles, Prince Brainard (Journal of Learning for Development, 2020)
To meet the growing demand for continuing professional development of practising teachers, the integrated in-service teacher training (INSET) programme aims at making permanent improvements on the quality of teaching and learning for Junior Secondary School (JSS) Teachers in Sierra Leone. Within this context, a toolkit for School-Based Teacher Development was created and microlearning identified as an ideal mode to deliver the toolkit content. In this paper, we present the design considerations that informed this decision as well as challenges and lessons learned from the first implementation of the INSET project for junior secondary school teachers in Sierra Leone. A multimodal approach was considered and implemented to mitigate Internet access challenges and to expand learning opportunities. These include a mobile app version of the Toolkit, offline access to microlearning resources on the TeacherFutures platform via the Moodle mobile app, a mobile app version of one INSET module, an e-portfolio to be used by participants in sharing their learnings as demonstrated and practised during a face-to-face roll-out seminar, and finally, WhatsApp groups in which different schools engaged in discussions based on the questions on the Toolkit. Preliminary findings indicate a strong preference among participants for the use of WhatsApp as the main channel of communication within the communities of practice; and very limited use of the main e-learning Moodle platform and e-Portfolio. This necessitates a need to critically evaluate the effectiveness of the design of a multimodal approach for delivering microlearning content. From this, we seek to establish a set of design considerations, capacity building and technical support issues derived from analysis of data emerging from the ongoing project rollout. This will inform future integration of Microlearning resources in the teacher training project.
Keywords: Barriers; Communities of Practice; Electronic Learning; Foreign Countries; Inservice Teacher Education; Integrated Learning Systems; Internet; Multimedia Materials; Portfolios (Background Materials); Professional Continuing Education; Professional Development; Program Effectiveness; Secondary School Teachers; Social Media; Synchronous Communication; Teacher Collaboration; Teacher Competencies; Workshops

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
Keywords: auto_merged

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
Keywords: ⛔ No DOI found

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode